Thermal behavior and densification during selective laser melting of Mg-Y-Sm-Zn-Zr alloy: simulation and experiments. (25th November 2020) - Wang, Wenli; Wang, Dan; He, Lun; Liu, Wenqiang; Yang, Xin
Abstract: The temperature field and flow field during the selective laser melting (SLM) process of Mg-3.4Y-3.6Sm-2.6Zn-0.8Zr alloy were simulated by using a re-developed Fluent 17.0 commercial finite volume method (FVM). The surface tension, Marangoni convection, and the laser heat source with Gaussian distribution are taken into account. The effects of laser power and scanning speed on the temperature and the size of the molten pool are studied, and the influence of line energy density (LED) on the flow and densification behavior of the molten pool is also discussed. It shows that the temperature and the size of the molten pool are positively correlated with the laser power, and negatively correlated with the scanning speed. The LED affects the flow of the molten pool and the movement of the bubbles, thereby affecting the densification behavior. For an optimized laser power of 50 W and scanning speed of 0.4 m s −1, the bubbles can escape smoothly, the existence time of the molten liquid is 355.58 μ s and a molded part with the optimal density (95.98 ± 1.4)% is obtained. The experimental and numerical simulation results are in good agreement. It is concluded that a laser power of 50 W, and a scanning speed of 0.4 m s −1 are the optimal process parameters.